2011
DOI: 10.1149/2.059112jes
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation Mechanism of Indium and Gallium during Electrodeposition of Cu(In,Ga)Se2 Thin Film

Abstract: The incorporation mechanism of Indium and Gallium during electrodeposition of Cu(In,Ga)Se 2 thin film from chloride electrolytes using sodium sulfamate as a complexing agent has been investigated by means of cyclic voltammetry (CV) coupled with EDS and Raman techniques. Cyclic voltammetry study was performed in unitary Cu, In, Ga and Se systems, binary Cu-Se system, ternary Cu-In-Se and Cu-Ga-Se systems, and quaternary Cu-In-Ga-Se system. EDS and Raman analysis were carried out to determine the evolution of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The inhibition effect of sodium sulfamate on this reaction in Cu-Se binary system is much weaker than that in Cu unitary system, which might be because sodium sulfamate prefers to work on H 2 SeO 3 . According to the CV analysis in H 2 SeO 3 solution with different concentrations of CuCl 2 [33], the following reduction peak A at about À0.25 V corresponds to the reaction involving Cu + and H 2 SeO 3 preceded by Eq. (6), and the large peak B at about À0.35 V is attributed to formation of CuSe by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition effect of sodium sulfamate on this reaction in Cu-Se binary system is much weaker than that in Cu unitary system, which might be because sodium sulfamate prefers to work on H 2 SeO 3 . According to the CV analysis in H 2 SeO 3 solution with different concentrations of CuCl 2 [33], the following reduction peak A at about À0.25 V corresponds to the reaction involving Cu + and H 2 SeO 3 preceded by Eq. (6), and the large peak B at about À0.35 V is attributed to formation of CuSe by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…They proposed that the insertion of In and Ga into the solid phase might proceed by an underpotential deposition mechanism which involved two different routes: In 3+ and Ga 3+ reduction by a surface-induced effect from Cu 3 Se 2 and/or a reaction with H 2 Se. The same research group also reported 80) the incorporation mechanism of gallium during electrodeposition of Cu(In,Ga)Se 2 thin film from chloride electrolytes using sodium sulfamate as a complexing agent. The insertion of gallium involved two different routes: firstly, Ga 3+ reacted with H 2 Se to form gallium selenide (Ga 2 Se 3 ); secondly Ga 2 O 3 was formed via hydrolysis of Ga 3+ due to the increase of local pH.…”
Section: Electrodeposition Of Gallium Alloysmentioning
confidence: 94%
“…11b) (Fig. 11c) for as-deposited and for annealed CIGSe thin films at 174 and 176 cm −1 , suggesting that the Ga 2 Se 3 phase must be in the dispersed nano-crystalline form which involves in the phase formation only during annealing [109].…”
Section: Electrochemical Formation Mechanism Of Cise/cigsementioning
confidence: 95%